The IR-resummed Effective Field Theory of Large Scale Structures - Senatore, Leonardo; Zaldarriaga, Matias (Journal of cosmology and astroparticle physics, 2015)
We develop a way to describe analytically the effect of large displacements of galaxies that occur in our universe, and that were affecting our capability to predict the distribution of galaxies in our universe.